2010
DOI: 10.1111/j.1420-9101.2010.02022.x
|View full text |Cite
|
Sign up to set email alerts
|

Altruistic self‐removal of health‐compromised honey bee workers from their hive

Abstract: Social insect colonies represent distinct units of selection. Most individuals evolve by kin selection and forgo individual reproduction. Instead, they display altruistic food sharing, nest maintenance and self‐sacrificial colony defence. Recently, altruistic self‐removal of diseased worker ants from their colony was described as another important kin‐selected behaviour. Here, we report corroborating experimental evidence from honey bee foragers and theoretical analyses. We challenged honey bee foragers with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
137
2
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(150 citation statements)
references
References 43 publications
8
137
2
3
Order By: Relevance
“…However, the sharp decrease in the survival rate of infected bees inside the hive could still be due to the combined effects of the ''hygienic behaviours'' carried out by resident workers as well as self-removal of infected bees. Altruistic self-removal of infected honeybee workers from their hive has been suggested by Shimanuki et al (1994) and Kralj and Fuchs (2006), and more recently was demonstrated by Rueppell et al (2010). Nevertheless, during the first 10 min, healthy bees were bitten and groomed significantly less than infected bees, while significantly more infected bees were dragged outside the hives.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, the sharp decrease in the survival rate of infected bees inside the hive could still be due to the combined effects of the ''hygienic behaviours'' carried out by resident workers as well as self-removal of infected bees. Altruistic self-removal of infected honeybee workers from their hive has been suggested by Shimanuki et al (1994) and Kralj and Fuchs (2006), and more recently was demonstrated by Rueppell et al (2010). Nevertheless, during the first 10 min, healthy bees were bitten and groomed significantly less than infected bees, while significantly more infected bees were dragged outside the hives.…”
Section: Discussionmentioning
confidence: 78%
“…Like all animals, individual honeybees recruit physiological and immunological defence against disease agents (Evans et al, 2006;Schmid et al, 2008;Wilson-Rich et al, 2008). Moreover, as well as individual immunity, honeybees also show several physiological, behavioural and organizational colony-level adaptations such as spatial and behavioural compartmentalization of worker bees on the nest (Naug and Camazine, 2002;Naug, 2008), social fever (Starks et al, 2000), nest construction and enrichment with antimicrobial material (Simone et al, 2009;Baracchi and Turillazzi, 2010;Baracchi et al, 2011), grooming (Kolmes, 1989;Boecking and Spivak, 1999), hygienic behaviour (Rothenbuhler and Thompson, 1956;Spivak and Gilliam, 1998a,b;Richard et al, 2008), undertaking (Visscher, 1983) and self-removing (Kralj and Fuchs, 2006;Naug and Gibbs, 2009;Rueppell et al, 2010). Behaviour, in particular, plays an important role in infection control: removal, quarantine or exile of infected individuals can reduce the exposure of a population once disease takes hold (Clancy, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…While theoretical work convincingly revealed the conditions required for host suicide to evolve [39,40], empirical work has often been criticized [41,42]. In particular, the adaptive significance of host suicide has been challenged because studies involved eusocial Hymenoptera [43][44][45] or clonal aphids [46], where complex life histories impeded rigorous fitness tests and the exclusion of agarose concentration in growth medium bacterial cultures went extinct ** *** *** *** *** * *** *** *** *** ** *** *** *** *** Figure 3. (a) On solid agarose (0.4%, high relatedness) Escherichia coli l significantly outcompeted E. coli HK97 at all phage concentrations, even when initially rare (t-tests, from left to right: t 7 ¼ 3. rspb.royalsocietypublishing.org Proc R Soc B 280: 20123035 alternative explanations.…”
Section: Discussionmentioning
confidence: 99%
“…Possible examples include the observation that infected social insect workers leave the colony to die in isolation (i.e. altruistic self-removal [44,45]), a behaviour that could come at negligible costs because infected individuals might be strongly compromised in carrying out worker tasks anyway.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, mortality results from a specialized, non-aggressive task that has evolved to ensure colony survival. A third class of suicidal defense, termed host suicide or altruistic self-removal, occurs when sick individuals leave the nest to die in isolation, which lowers the risk of infecting nestmates (Heinze and Walter, 2010;Rueppell et al, 2010). As in the two previous cases, colony fitness is presumably increased by individual self-sacrifice.…”
Section: Introductionmentioning
confidence: 99%